2007
DOI: 10.1074/jbc.m604801200
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of AP-1 Proteins in Collagen Gel-induced Epithelial Cell Apoptosis Mediated by Low Substratum Rigidity

Abstract: In this study, we established that collagen gel, but not collagen gel coating, induced apoptosis exclusively in epithelial cell lines, which indicated that low substratum rigidity might trigger cell apoptosis. To confirm this, we used collagen gels with different rigidities due to cross-linking or physical disruption of collagen fibrils caused by sonication. We found that collagen gel-induced apoptosis was inversely correlated with substratum rigidity. Low substratum rigidity collagen gel-induced apoptosis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 67 publications
4
23
1
Order By: Relevance
“…Moreover, our recent study showed that low substratum rigidity-induced apoptosis is inversely correlated with substratum rigidity. Nevertheless, a significant difference of apoptosis ratio still exists when cells are cultured under substratum rigidity between 20 and 103 Pa (52), in which range ␤ 1 -integrin is neither activated nor clustered. We noted that other stretch-activated ion channels or capacitative calcium entries may be involved in detecting matrix rigidity at this range (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, our recent study showed that low substratum rigidity-induced apoptosis is inversely correlated with substratum rigidity. Nevertheless, a significant difference of apoptosis ratio still exists when cells are cultured under substratum rigidity between 20 and 103 Pa (52), in which range ␤ 1 -integrin is neither activated nor clustered. We noted that other stretch-activated ion channels or capacitative calcium entries may be involved in detecting matrix rigidity at this range (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…However, resent studies showed that sensing mechanical stimuli is also crucial for cells to detect several useful signals from the external environment during development and tumorigenesis (14,15,27,42,51). The three-dimensional collagen gel culture system has been used as a model to study ECM signaling because it provides not only biochemical signals but also biophysical properties (52,53). The elastic modulus of soft tissue is in the few hundreds to several thousands of pascals range that can be made by collagen gel (37,46,57).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…35 D1 cells (1×10 6 per injection) were harvested and mixed with the collagen gel. Experimental groups included cells treated with 1 µM simvastatin (SIM), and 1 µM SIM mixed with Y27632 (10 µM), blebbistatin (Blebb) (10 µM), or cytochalasin D (CD) (0.5 µM), respectively, and untreated controls.…”
Section: Mouse Model Of Ectopic Bone Formationmentioning
confidence: 99%
“…57 For example, low substratum rigidity as been shown to trigger apoptosis in epithelial cells. 58 Artificial scaffold systems are ideal tools in which to study such principles in that they can be tailored to match the mechanical conditions encountered by tissues in vivo. This is an exciting area of research considering that the tumor microenvironment is known to be stiffer than normal tissue 59 and stem cells have been shown to direct their differentiation pathways depending on the nature of the mechanical environment.…”
Section: Wwwlandesbiosciencecommentioning
confidence: 99%